PEMETAAN AKSES HALAMAN SITUS WEB BERBASIS LOG-ACCESS (Log-Access Based Web Site Access Mapping Page) - Dison Librado; Wagito Wagito (Lembaga Penelitian dan Pengabdian Masyarakat - Universitas Teknologi Digital Indonesia, 2018)
STMIK AKAKOM as a private university has long utilized internet technology as a medium of information and communications. Various information provided on the official website of this campus is Home, Akakom Profile, Study Program / Department, Campus Info, News, General Archives, and more. However, there is no study of how the site is visited by users. A review of the pages covered is useful for the evaluation of the site. The study aims to see the number and mapping of visits per page of the site.The steps taken are literature studies from relevant reference sources, configuring the Apache web server, collecting log data access for a certain time, then processing log access data, making discussion of the results of data processing, and making conclusions. Processing log access is done by changing the format of log access into csv format. Furthermore csv format changed to MySQL database format. The next processing is done using SQL commands. The results are presented in the form of information on the number of visitors on the site page, the pattern of visits and identification of frequently visited sites pages.The result of the research shows that the category most interested by visitors is News, followed by Campus Info category, then Akakom Profile, Study Program / Department, Others, and the last category is General Archive. The results of the research are expected to be used to assist the managers and developers in order to improve the quality of information services.